Persepsi Pemilik Kos Terhadap Pentingnya Laporan Keuangan dalam Pengambilan Keputusan Bisnis - Pera Purwanti; Basis Gumilarsih Andamari (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
This study aims to analyze boarding house owners’ perceptions of the importance of financial statements in business decision-making. Although boarding house businesses continue to grow, many owners have not optimally utilized financial statements in managing their businesses. This research uses a qualitative descriptive approach with a case study method. Data were collected through interviews, observation, and documentation involving five boarding house owners in Jakarta. The results indicate that owners generally perceive financial statements as important for controlling and evaluating business performance; however, their level of understanding and implementation varies. The main obstacles include limited accounting knowledge, time constraints, and the mixing of personal and business finances. Financial analysis using Return on Investment (ROI) and Break Even Point (BEP) shows that financial statements support more rational and effective business decision-making.